2021
DOI: 10.1109/ojits.2021.3093712
|View full text |Cite
|
Sign up to set email alerts
|

Use of Naturalistic Driving Studies for Identification of Vehicle Dynamics

Abstract: This paper discusses the feasibility of data captured in a long-term Naturalistic Driving Study (NDS) for identification of vehicle dynamics. Driving data were captured for over a year. In this data capture, there was minimal effort to define or control everyday driving practices. While the use of real-world data for model parameter identification is a well-known method, NDS are commonly used to explore the behavior of drivers or to analyze real-world traffic situations. Data from NDS have not yet been used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The former requires a vehicle model. This model is often non-linear [9] [10] [11] [12] and its parameters are not always easy to identify [13] [14]. Vehicle models can be divided into two categories: kinematic and dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…The former requires a vehicle model. This model is often non-linear [9] [10] [11] [12] and its parameters are not always easy to identify [13] [14]. Vehicle models can be divided into two categories: kinematic and dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…Albers et al [2] showed the prospective of automotive development processes driven by sensor data. More specifically, Reicherts et al [3] used naturalistic driving studies to identify vehicle dynamics. Tanshi and Söffker [4] proposed a method for determining the takeover time budget based on the analysis of driver behavior.…”
Section: Introductionmentioning
confidence: 99%